The Age-Wealth Relationship: A Cross-Section and Cohort Analysis - Shorrocks, A. F. (The Review of Economics and Statistics, 1975)
THE age profile of individual asset holdings is frequently supposed to follow a hump pattern, increasing during the working lifetime and declining in later years. The theoretical explanation of such a relationship is firmly established, since it is a characteristic feature of life-cycle saving models. However, the empirical evidence has never been critically examined. A number of studies based on sample survey information have been regarded as confirming this hump pattern, but on closer examination the evidence is far from conclusive. Moreover the survey results conflict fundamentally with alternative estimates of the age-wealth relationship derived from estate tax data. This paper begins in section II by examining this basic conflict. In the following section the relevance of cross-section studies is questioned, and a cohort is identified whose lifetime wealth characteristics can be studied. The sequence of observed wealth distributions for this cohort is obtained by selecting successive ten years age groups from the Estate duty statistics at intervals of a decade. Section IV is devoted to an analysis of the variation in the composition of any cohort as it ages. These composition changes arise from the fact that wealthier individuals have a lower mortality rate and therefore tend to become a larger proportion of the surviving cohort independently of accumulation behaviour. In these circumstances the characteristics of the representative individual will not necessarily correspond to the representative behaviour of the group. It is, however, possible to correct for this change in composition so that the empirical estimates can be compared with the predictions of economic theory.